Internalisasi Nilai Perjuangan Teuku Umar bagi Santri Dayah Darul Faizin Mengejar Cita-cita - Suhendra, Noval; Syahril, Syahril; Noviar, Helmi; Hatmawan, Aglis Andhita; Alisman, Alisman; Mahrizal, Mahrizal; Ansari, Leli Putri; Hadi, Fajri; Arisna, Puput; Hartini, Hartini (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity aims to internalize the values of Teuku Umar's struggle as an inspiration for students in achieving their dreams. This activity is based on the problems faced by traditional dayah, coupled with the existence of skeptical assumptions from the community that can affect the motivation and self-confidence of students. The approach used is a participatory educational approach by actively involving students and fostering good communication. This activity consists of two main sessions, namely interactive seminars and training on planning goals. The results of the study showed that the values of Teuku Umar's struggle could be internalized by students of Dayah Darul Faizin and also the building of students' self-confidence increased after the training, motivating them to continue fighting despite their limitations. This activity received a positive response from all participants, including teachers, and was considered useful in shaping the character of students.